The Concept of Internalizing Religious Moderation Through Multicultural Counseling - Suwito,; Fernando, Frendi; Masruri, Muhammad; Hartono, (Advances in Humanities and Contemporary Studies, 2024)
Diversity is a challenge for the Indonesian nation, because nowadays there is a rise in the behavior of people who commit violence in the name of religion. This can threaten the disintegration of the Indonesian nation, so there is a need for multicultural awareness. In an effort to overcome this problem, the government is trying to strengthen religious moderation in society, religious moderation is a middle ground between the diversity of religions in Indonesia. Diversity must be accommodated by the world of education, as the leading pillar in shaping character, positive attitude and attitude of acceptance of diversity. This can be done by internalizing religious moderation by using a multicultural and multireligious approach in the teaching and learning process as well as in the student service process. One way that is considered capable of being a conceptual offer to build an attitude of religious moderation is through multicultural counseling, because it is considered capable of being a guide in building the character and self-confidence of students in the present and in the future. In addition, it can be a conceptual offer of a moderate inclusive education organization in accordance with the goals of religious moderation itself. Therefore, every counselor is expected to be able to understand the cultural background of students in order to create a generation of nation's children with moderate character.